Pelatihan Baca Tulis Arab Pegon Madrasah Diniah Desa Sumberpakem - Ahmad Muzayyin; Olivia Dwi Febyanti; Ifadah Maziah Baidillah; Muhammad Syahrul Ardhana; Erlinda Eka Maeliyanti; Nafisatul Aini; Moh Rizal Amin; Nikmatun Nadhiro; Moh. Abdillah Zaini; Nova Kurnia Hasan; Nailatul Amaliyah; Mohammad Ramadhan Setiawan; Dicky Irwansyah; Mohammad Robith Mas’ud; Nurul Hasanah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Madrasah diniah is a non-formal educational institution that has a strategic role in learning yellow books that use Arabic Pegon. However, there are limitations in the ability to read and write Arabic Pegon in Madrasah diniah in Sumberpakem village. The purpose of this study is to improve the ability and uniformity of reading and writing Pegon in the form of training in reading and writing Arabic Pegon in Madrasah diniah Sumberpakem. The method used is Participatory Action Research (PAR) with a qualitative approach, involving the management of Madrasah diniah Sumberpakem, Ustadz / Ustadzah, and students with a series of stages of initial identification, collaborative mapping, formulating strategies, implementing change actions, evaluating and reviewing. The results of the study showed a significant increase in reading and writing Arabic Pegon. In addition, this study can encourage the sustainability of reading and writing Arabic Pegon based on clear sources of teaching materials.